2013
DOI: 10.1128/jcm.01874-13
|View full text |Cite
|
Sign up to set email alerts
|

“Epidemic Clones” of Listeria monocytogenes Are Widespread and Ancient Clonal Groups

Abstract: The food-borne pathogen Listeria monocytogenes is genetically heterogeneous. Although some clonal groups have been implicated in multiple outbreaks, there is currently no consensus on how "epidemic clones" should be defined. The objectives of this work were to compare the patterns of sequence diversity on two sets of genes that have been widely used to define L. monocytogenes clonal groups: multilocus sequence typing (MLST) and multi-virulence-locus sequence typing (MvLST). Further, we evaluated the diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
115
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 62 publications
(117 reference statements)
12
115
0
1
Order By: Relevance
“…Among these, 185 were analyzed previously by MLST (6,7,15), whereas the MLST genotypes of the 97 remaining strains were determined in the present study. The latter strains were selected from the Collection of Listeria of the Institut Pasteur (CLIP) maintained at the French National Reference Centre and the WHO Collaborating Centre for Listeria.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 185 were analyzed previously by MLST (6,7,15), whereas the MLST genotypes of the 97 remaining strains were determined in the present study. The latter strains were selected from the Collection of Listeria of the Institut Pasteur (CLIP) maintained at the French National Reference Centre and the WHO Collaborating Centre for Listeria.…”
mentioning
confidence: 99%
“…The large-scale application of MLST led to the identification of numerically predominant and internationally widespread clonal complexes (CCs), which are considered clones, i.e., sets of isolates descending from a single common ancestor (5-9). Most major clones have been involved in outbreaks of listeriosis (7,(10)(11)(12). Rapid identification of MLST clones is important for epidemiological surveillance and outbreak investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher level of sequence polymorphisms associated with MVLST has enabled local epidemiological studies, often differentiating outbreak and epidemic strains from other isolates (17,18). Cantinelli et al (19), however, recently compared 125 L. monocytogenes strains and found that MVLST and MLST provided similar sequence types (STs), phylogenetic clustering, and discriminatory power. Mutations in virulence genes are associated with a reduced invasion phenotype in L. monocytogenes.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first report of non-H 2 S-producing S. Senftenberg bacteria in the world. In this study, the microbiological and genetic characteristics of the non-H 2 S-producing and selected H 2 S-producing S. Senftenberg isolates were determined using a biphasic approach consisting of phenotypic (biochemical, serological, and antimicrobial susceptibility) and molecular (pulsed-field gel electrophoresis [PFGE], multilocus sequence typing [MLST], and clustered regularly interspaced short palindromic repeat [CRISPR]) analysis (15)(16)(17)(18)(19). The molecular mechanism behind the lack of H 2 S production was also explored.…”
mentioning
confidence: 99%